The Impact of the SQ3R Method on Physics Concept Understanding and Learning Outcomes in Measurement Material - Aini, Rohmatul; Koryataini, Lia; Suprianto, Suprianto; Hidayati, Nurul; Rihana, Rihana (Lombok Institute, 2024)
This study aims to evaluate the effectiveness of the SQ3R method in improving student learning outcomes and understanding of physics concepts related to measurements among class X-I students at SMA Negeri 3 Pamekasan. Conducted as classroom action research (CAR) with 36 participants, data were collected through a five-question test. Prior to implementing the SQ3R method, the average student score was 56.67, with a learning completion rate of 22.22%, indicating that 28 students had not achieved an adequate understanding of the material. Post-implementation, the average score increased to 75.28, with a learning completion rate of 61.11%, signifying successful comprehension for 22 students and an average improvement of 38.89%. In Cycle II, which focused on analyzing single and repeated measurements, the average score rose to 82.22, with an 86.11% completion rate, though five students (13.88%) remained below the required standard. Additionally, the SQ3R method positively impacted student engagement. In Cycle I, physical, mental, and emotional activities were recorded at 50.57%, 35.67%, and 61.11%, respectively. These metrics increased significantly in Cycle II to 86.27%, 92.24%, and 87%. These findings demonstrate the SQ3R method's effectiveness in enhancing learning outcomes, conceptual understanding, and student participation.